Obtenção e caracterização de membranas poliméricas produzidas a partir da técnica de eletrofiação, para remoção do fármaco cloridrato de tetraciclina - Pagno, Vanessa (2018)
Environmental concerns over emerging pollutants detected in aquatic environments, especially in wastewater, have increased in recent years. Among these contaminants, antibiotics call attention because of the risks they can bring to the microorganisms present in the environment, posing a trigger for resistance to bacteria, bringing serious consequences to human and animal health. Among the main antibiotics found in wastewater, tetracyclines stand out due to their high consumption, mainly in harmaceutical drugs and human therapy. Facing this environmental problem, several techniques have been studied to minimize this situation, such as adsorption by means of porous materials such as activated carbon, resins and adsorbent membranes. The objective of this work was to obtain and characterize polymer membranes produced by the electrophying technique using biodegradable polymers, with and without heat treatment, for the removal of the drug tetracycline hydrochloride. The polymers used were poly (?-caprolactone) (PCL) polybutylene adipate-co-terephthalate (PBAT), chitosan (CS) and polyethylene oxide (PEO), with addition of activated charcoal biomass of Brazil nut (CA-BCB) and commercial charcoal of babassu coconut husk (Ca-CB)) in the polymer solutions. This work is divided into two scientific articles, the first one is obtained PBAT / PCL membranes with and without heat treatment and PBAT / PCL / CABCB membranes with and without heat treatment. In the second, PBAT-PCL membranes with thermal treatment, and PBAT-PCL-CA with thermal treatment, both with the surface-electrophysed Chitosan-PEO blends are obtained. In the two articles all the membranes produced were characterized: by morphology, Scanning Electron Microscopy (SEM); molecular structure of the blends, Infrared Spectroscopy with Fourier Transform (FTIR); thermal behavior, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC); crystallinity, X-ray diffraction (XRD); and wettability of the surface (contact angle). In the first article, the incorporation of CA-BCB promoted a greater stretching of the fibers and reduction of their average diameters, a fact proven with the analyzes of SEM.; There was a decrease in crystallinity, as indicated in the DSC curves, same behaviors were observed for the heat treatment of the membranes. The FTIR analysis showed that the chemical structure of the polymers was not altered. With the contact angle analysis, it was verified that the membranes have hydrophobic character, which increases with the heat treatment. With tetracycline hydrochloride (CTC) drug stripping tests, the membranes were found to have na initial removal capacity of 67% with the addition of CA-BCB as a filler. In the second article, changes in the thermal properties of the blends were observed, the addition of commercial activated charcoal of babassu coconut (CA-CB) and reduction of the crystallinity of the polymers, as evidenced by the DSC analysis. With the FTIR analysis, characteristic bands were verified for the two blends, PBAT-PCL and Chitosan-PEO. The contact angle reduced with the presence of the Chitosan-PEO blends on the surface, showing a more hydrophilic character, and increased with the addition of activated carbon, presenting a more hydrophobic character. CTC drug removal tests were performed at different concentrations 100, 200 and 500 mg L-1. For the higher concentration, a removal capacity of approximately 80% was observed, indicating that surface modifications, addition of Ca-CB, heat treatment and addition of the Chitosan-PEO blend favor its application in the removal of CTC from waste water.